ADUBAÇÃO VERDE EM CULTIVO ORGÂNICO DE HORTALIÇAS - Ambrosano, Edmilson José; Rossi, Fabrício; Tamiso, Luciano Grassi; Mello, Paulo César Tavares de; Schammass, Eliana Aparecida; Guirado, Nivaldo; Tessarioli Neto, João (REVISTA DE AGRICULTURA, 2015)
ADUBAÇÃO VERDE EM CULTIVO ORGÂNICO DE HORTALIÇAS